‘Soglitude’- introducing a method of thinking thresholds - Tatjana Barazon (Conserveries Mémorielles)
‘Soglitude’ is an invitation to acknowledge the existence of thresholds in thought. A threshold in thought designates the indetermination, the passage, the evolution of every state the world is in. The creation we add to it, and the objectivity we suppose, on the border of those two ideas lies our perceptive threshold. No state will ever be permanent, and in order to stress the temporary, fluent character of the world and our perception of it, we want to introduce a new suitable method to think change and transformation, when we acknowledge our own threshold nature. The contributions gathered in this special issue come from various disciplines: anthropology, philosophy, critical theory, film studies, political science, literature and history. The variety of these insights shows the resonance of the idea of threshold in every category of thought. We hope to enlarge the notion in further issues on physics and chemistry, as well as mathematics. The articles in this issue introduce the method of threshold thinking by showing the importance of the in-between, of the changing of perspective in their respective domain. The ‘Documents’ section named INTERSTICES, includes a selection of poems, two essays, a philosophical-artistic project called ‘infraphysique’, a performance on thresholds in the soul, and a dialogue with Israel Rosenfield. This issue presents a kaleidoscope of possible threshold thinking and hopes to initiate new ways of looking at things.For every change that occurs in reality there is a subjective counterpart in our perception and this needs to be acknowledged as such. What we name objective is reflected in our own personal perception in its own personal manner, in such a way that the objectivity of an event might altogether be questioned. The absolute point of view, the view from “nowhere”, could well be the projection that causes dogmatism. By introducing the method of thinking thresholds into a system, be it philosophical, artistic or scientific, it tends to free itself from rigid or fixed models and accepts change and development as the fundamental nature of things. Thinking thresholds as a method of thought progress cannot be done in a single process and therefore asks for participation in its proper nature. The soglitude springs namely from the acceptance of a multitude of points of view, as it is shown by the numerous contributions we present in this issue ‘Seuils, Thresholds, Soglitudes’ of Conserveries mémorielles.